Inovasi dan Tantangan Pengembangan Kurikulum Pendidikan Islam di Indonesia dalam Menghadapi Transformasi Digital - Moh. Kusno (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
In facing the digital era, Islamic education needs to adapt, one of which is through curriculum renewal or development. This is important because the curriculum plays a central role as a reference and a determinant of educational success. This research aims to identify the challenges and opportunities in developing the Islamic education curriculum in facing the digital era and to provide solutions to overcome various challenges and leverage the opportunities in this digital age. This research employs a descriptive qualitative approach, utilizing two types of data sources: primary and secondary data. The data collection technique involves library research by reviewing literature related to the chosen topic. The challenges and opportunities highlight the importance of integrating Islamic values into the development of the Islamic education curriculum as a form of educational transformation to respond to the digital era. By understanding the various challenges, relevant and sustainable improvements can be made to enhance the quality of Islamic education. By recognizing the opportunities in the digital era, these can be utilized to improve resource quality and achieve the goals of Islamic education.